Reconsidering Lease Impacts: A Spatial Ecology Analysis of Aquaculture–Habitat Interactions - Kenosky, Jason (My University, 2025)
Oyster aquaculture and submerged aquatic vegetation (SAV) are both critical components of coastal ecosystem function, yet their spatial and ecological interactions remain poorly understood at landscape scales. This study presents a multi-decadal, spatially explicit analysis of SAV structure in relation to oyster aquaculture leases in Maryland’s mid-Chesapeake Bay. Using GIS-based modeling and statistical approaches including generalized additive models, factorial linear models within a BACI (Before–After Control–Impact) design and Bayesian hierarchical modeling, I tested three hypotheses related to temporal alterations in SAV structure, the influence of lease proximity and the role of lease configuration. My findings reveal that while SAV area has increased over time, fragmentation and patch isolation have also intensified, particularly on the Eastern Shore, suggesting potential declines in ecosystem resilience. Surprisingly, SAV patches near active oyster leases exhibited greater cohesion and complexity post-activation in several cases, challenging the assumption that aquaculture infrastructure inherently degrades seagrass habitats. Lease configuration variables, including cage density and alignment, had weak and inconsistent effects compared to broader site-level environmental conditions. These results emphasize the need for long-term, spatially explicit monitoring and suggest that aquaculture and habitat restoration goals may be compatible under certain environmental contexts. Adaptive permitting frameworks that account for local biophysical settings, rather than rigid exclusion zones, may better support both sustainable aquaculture development and coastal ecosystem recovery.
This project analyzes how oyster aquaculture affects submerged aquatic vegetation (SAV) structure in Maryland’s Chesapeake Bay using spatial modeling, seascape ecology, and multi-decadal GIS data to assess habitat fragmentation, connectivity, and potential for ecosystem coexistence.
Keywords: Submerged Aquatic Vegetation; Chesapeake Bay, MD; GIS Modeling; Patch Dynamics; Ecological Resilience; Landscape Connectivity